2014
DOI: 10.18352/bmgn-lchr.450
|View full text |Cite
|
Sign up to set email alerts
|

Nested governance for effective REDD+: Institutional and political arguments

Abstract: Abstract:Reducing Emissions from Deforestation and Forest Degradation and Forest Enhancement (REDD+) has become a central focus of global climate change mitigation efforts. Even though the international demand for forest-based carbon sequestration is the key driver of REDD+, forest protection strategies must be implemented on the ground. This cross-scale nature of REDD+ explains why scholars and policy makers increasingly favor nested governance arrangements over either fully centralized or fully decentralized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Top-down solutions encounter problems, such as resistance among local actors, which impedes progress (Moeliono et al 2014 ; Sanders et al 2017 ), although even highly centralized spaces can give people room to maneuver and try new things (Pham et al 2014 ). Other studies have demonstrated the importance of forest users’ and inter-community forestry associations’ participation in REDD+ activities along with the support of government agencies and higher-level institutional arrangements (Kashwan and Holahan 2014 ).…”
Section: Multilevel Governance and Redd+mentioning
confidence: 99%
“…Top-down solutions encounter problems, such as resistance among local actors, which impedes progress (Moeliono et al 2014 ; Sanders et al 2017 ), although even highly centralized spaces can give people room to maneuver and try new things (Pham et al 2014 ). Other studies have demonstrated the importance of forest users’ and inter-community forestry associations’ participation in REDD+ activities along with the support of government agencies and higher-level institutional arrangements (Kashwan and Holahan 2014 ).…”
Section: Multilevel Governance and Redd+mentioning
confidence: 99%
“…The final design principle is nested governance (P8). In Ostrom's framework, this principle requires preserving community autonomy from higher levels of government within a nested system (Kashwan and Holahan, 2014). For policing, this reflected explicitly in community autonomy over-policing.…”
Section: Ostrom-compliant Policingmentioning
confidence: 99%
“…The tropical forests in Latin America, the Caribbean, Africa and Asia are characterized by their complexitythe diversity of their species, short days, constant photoperiodicity, homogenous temperature, and the absence of thermal and hydrological stations (Whitmore 1983;Poorter and Bongers 1993;Lamprecht 1990). Approximately 800 million people live in these zones (Groom and Palmer 2012;Kashwan and Holahan 2014) of which 38% are undernourished (FAO, FIDA and PMA 2015). Fortunately, due to ancestral and traditional knowledge of the rural areas, which includes knowledge of the indigenous biodiversity of organisms that can be used as food, the percentage of undernourished is not likely to rise (Bennett 2002;Cole et al 2014).…”
Section: Introductionmentioning
confidence: 99%